Age and growth of the greater weever, Trachinus draco (Linnaeus, 1758) inhabiting Iskenderun Bay, North-eastern Mediterranean Sea - Buz, Kagan; Basusta, Nuri (Cahiers de Biologie Marine, 2015)
This study was carried out to determine the age and growth characteristics of Trachinus draco in the Northeastern Mediterranean during 2013-2014 fishing season. A total 532 Trachinus draco ranged from 13.5 to 32.0 cm in total length was caught by trawl and gill nets. The population consists of 45.89% for females and 54.11% for males. The total length-weight relationship was estimated as W = 0.0077 x TL2.95. The parameters of von Bertalanffy growth fitted to the mean observed total lengths-at-age for each sex separately and estimated as L-infinity = 43.994 cm, K = 0.087 year(-1), t(0) = -3.044 years for females, as L-infinity = 40.271 cm, K = 0.099 year(-1), t(0) = -2.799 years for males and as L-infinity = 46.445 cm, K = 0.076 year(-1), t(0) = -3.289 years for combined sexes. In fish between age groups 2 and 3, the maximum absolute growth was estimated as 2.47 cm and relative growth was calculated as 16.46%. On the other hand, in fish between age groups 9 and 10, absolute growth was estimated as 1.21 cm and relative growth was calculated as 4.36%. Population condition factor value was 0.654 +/- 0.021; the highest condition factor was found as 0.692 in fish at age 9.
Keywords: Greater weever; Trachinus draco; Age; Growth; North-eastern Mediterranean